Analisis Pengaruh Waktu Las dan Kuat Arus Spot Welding terhadap Kekuatan Tarik pada Stainless Steel 304 - Taher, Bruce Heofilus; Rosehan, Rosehan; Lubis , Sobron Yamin (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to find out how much electric current is right so that spot welding becomes more efficient and to find out which is the best way so that the welding results have good results. The type of research used in this study used a type of literature study. Preparation of tools and specimens with AWS D8.9. Based on the results of the test data obtained, it shows that the greater the welding current used, the strength of the resulting welded joint becomes stronger, in the results of the tensile strength test data obtained, namely specimens with a current of 2.28 volts have greater tensile strength results compared to 1.75 volt specimen if the time used is the same. Then the greater the welding time on the spot welding machine, the stronger the strength of the welded joints produced in the spot welding process, this can be shown in the results of the tensile strength test data obtained, namely specimens with 3 seconds of time have greater tensile strength results than with the specimen with a time of 1 second if using the same current strength. Lastly, the elastic modulus value is inversely proportional to the current and time used during welding, shown in the results of the tensile strength test data obtained, namely specimens with a current of 1.75 volts and a time of 1 second have a greater modulus value than specimens with a current of 2. 28 volts and 3 seconds time.